2017
DOI: 10.1038/eye.2017.97
|View full text |Cite
|
Sign up to set email alerts
|

Stepping into the virtual unknown: feasibility study of a virtual reality-based test of ocular misalignment

Abstract: IntroductionDissociated tests of strabismus provide valuable information for diagnosis and monitoring of ocular misalignment in patients with normal retinal correspondence. However, they are vulnerable to operator error and rely on a fixed head position. Virtual reality headsets obviate the need for head fixation, while providing other clear theoretical advantages, including complete control over the illumination and targets presented for the patient's interaction.PurposeWe compared the performance of a virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
(7 reference statements)
0
20
0
Order By: Relevance
“…IVR in HMD is an emerging and very promising visual rehabilitation approach using high-technology devices (52)(53)(54)(55)(56). It is developed to provide perceptual learning with better ecological validity due to virtual reality, greater flexibility due to home-based stimulation protocol, and improved efficiency due to patient-tailored protocols (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…IVR in HMD is an emerging and very promising visual rehabilitation approach using high-technology devices (52)(53)(54)(55)(56). It is developed to provide perceptual learning with better ecological validity due to virtual reality, greater flexibility due to home-based stimulation protocol, and improved efficiency due to patient-tailored protocols (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several studies on amblyopia and binocular vision using VR technology have also been conducted. A study about the improvement of visual acuity in patients with amblyopia through dichoptic training 2 , showed improvements in stereopsis in patients with intermittent exotropia 3 , and reported the assessment of ocular misalignment of strabismus patients through a dissociative test 13 . We have developed a system using HMD, combining the eye-tracking technology and VR, to measure the angle of strabismus with the principle of cover-uncover and alternate cover tests.…”
Section: Discussionmentioning
confidence: 99%
“…Learning to use the application would be easy for me 3. www.nature.com/scientificreports/ improvements in stereopsis in patients with intermittent exotropia 3 , and reported the assessment of ocular misalignment of strabismus patients through a dissociative test 13 . We have developed a system using HMD, combining the eye-tracking technology and VR, to measure the angle of strabismus with the principle of coveruncover and alternate cover tests.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…Li et al 14 reported that the degree of strabismus and stereopsis improved with dichoptic visual training using a VR platform in patients with intermittent exotropia. Nesaratnam et al 20 reported the rst use of a VR headset in assessing ocular misalignment and demonstrated its feasibility as the dissociative test for strabismus.…”
Section: Discussionmentioning
confidence: 99%